Intrusion of bilateral maxillary incisors with displacement of the labial alveolar cortical bone and a deformed nostril. Issue 3 (May 2015) - Kato, Takao; Iijima, Yosuke; Hino, Shunsuke; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract Maxillary central incisors are most commonly luxated during oral and maxillofacial trauma in children. In this paper, we describe a rare case of intrusion of both maxillary permanent central incisors in a 10-year-old boy who was involved in a traffic accident, resulting in upward displacement of the labial alveolar cortical bone and a deformed nostril. The information obtained from the plain CT images was not adequate, and 3D-CT images were very useful for precise diagnosis. In this patient with mixed dentition, a vacuum-formed splint proved to be effective for the fixation of the luxated teeth.